KNOWLEDGE, ATTITUDES, AND PRACTICES (KAP) TOWARDS POPULAR INDIGENOUS MUSIC OF SARAWAK: A PRELIMINARY SURVEY - Collin, Jerome; Ting, Su Hie; Esther, John Perry; Lim, Connie Keh Nie (2023)
Popular music by the indigenous people continues to gain popularity among the Malaysian masses despite being written and sung in vernacular languages. The present study examined this phenomenon by exploring the public perception of popular music produced by the indigenous people of Sarawak. Using the Knowledge, Attitudes, and Practices (KAP) survey method, the study gathered information from the general public about what is known (knowledge), believed (attitude), and done (practised) in the context of the rising popularity of Sarawak indigenous popular music. Preliminary results showed that most respondents possessed adequate knowledge of popular songs of the Iban, Bidayuh, Melanau, and Kenyah. The respondents held positive attitudes towards these songs and expressed them through shared music preferences and engagements such as listening, dancing, and singing. The respondents envisaged a role that Sarawak indigenous popular music plays in identity construction. The results revealed significant correlations between knowledge, attitudes, and practices of Sarawak indigenous popular songs among the study population. Further efforts and interventions are needed to ensure that popular music by the indigenous people of Malaysia can continue to flourish, considering its significant role in the lives of many Malaysians.